Gestão da informação esportiva no contexto da inteligência competitiva em clubes de futebol: um estudo de caso no Marília Atlético Clube - Jorge, Carlos Francisco Bitencourt [UNESP] (2013)
Information is an inherent component among all processes within an organization. In sports environment, there are several organizational processes which rely on information coming from different kinds of sports information sources, because from them, the decision-making information is made up, as well as the professional development. In sports environment, soccer, which is considered a national passion by the Brazilian society, stands out. Within soccer context, there are soccer clubs, institutions which are civil entities and the majority of them are unprofitable due to their structure and management model, whose central goal consists on promoting entertainment to population, and that automatically lifts up the passion by the referred sport. In the environment of football clubs is possible to observe a huge competitiveness. The club adopts effective management of information and work process of competitive intelligence (CI) can achieve competitive advantage against other clubs. From this perspective, the present research report aims at analyzing and making out the use of information in soccer clubs. In regard the methodological procedures, the ‘Study Case’ method has been picked out in order to be applied to Marília Atlético Clube (MAC), a sports club from Marília, upstate São Paulo, which answers the basic assumptions of the research purposes. Before the observations carried out in the Club, the management and uses of information from different hierarchy levels and sectors could be analyzed, as well as the form information is applied to obtain the competitive advantage. The research also emphasizes the importance of an information professional managing the management processes, both the IM and the CI. This way, it is intended to verify if the Club makes use of procedures regarding competitive intelligence, even if in an informal manner... (Complete abstract click electronic access below)